Anti–Citrullinated Protein Antibodies in Unaffected First‐Degree Relatives of Rheumatoid Arthritis Patients. Issue 6 (30th May 2013) - Barra, Lillian; Scinocca, Mathias; Saunders, Sheri; Bhayana, Rajesh; Rohekar, Sherry; Racapé, Maud; Coles, Robert; Cairns, Ewa; Bell, David A.
<x xml:space="preserve">Abstract</x> Objective First‐degree relatives (FDRs) of rheumatoid arthritis (RA) patients sharing genetic and environmental risk factors for RA may represent a pre‐RA state. Since anti–cyclic citrullinated protein/peptide antibodies (ACPAs) appear years before the onset of RA, the purpose of this study was to determine the prevalence of various ACPAs in FDRs of RA patients. Methods We evaluated 88 RA patients, 50 unaffected FDRs, and 20 healthy control subjects. Six different types of ACPAs were determined by enzyme‐linked immunosorbent assay. Joint and periodontal disease symptoms were self‐reported. Patients and FDRs were HLA typed for the shared epitope (SE) and the RA‐protective alleles HLA–DRB*1301/1302. Results FDRs had a high prevalence of ACPAs (48%) as compared to controls (10%). Prevalence of the SE and smoking in FDRs was also high (62% and 49%, respectively). Of all of the ACPAs in the FDRs, 13 of 32 (41%) were of the IgA isotype. The most commonly expressed IgG ACPA targeted citrullinated vimentin, occurring in 20% of FDRs. The FDRs had an average of 1 type of ACPA, whereas the RA patients expressed a median of 5 different ACPAs. The only FDR to later develop RA expressed 4 different ACPAs. Joint and periodontal disease symptoms in the FDRs were significantly associated with smoking (OR 5.714 [95% confidence interval (95% CI) 1.151–28.3] and OR 12.25 [95% CI 2.544–58.99], respectively), but not with ACPAs. Conclusion The rate of ACPA positivity in unaffected FDRs of RA patients with a high prevalence of the SE and smoking was 48%, whereas ACPAs were rare in the healthy controls. ACPAs in the FDRs of RA patients was most commonly of the IgA isotype, but IgG ACPA targeting citrullinated vimentin was also frequently found.